Effect of Participative Budgeting, Organizational Commitment and Work Motivation on Managerial Performance (Survey of Motor Vehicle Dealers in Bandung) - Arsalan, Syakieb; Haizam Mohd Saudi, Mohd; Susiani, Rini; Adison, Acep (International Journal of Engineering and Technology, 2018)
This research is aimed to find out the influence between participative budget, organization commitment and work motivation on the managerial performance of some automotive dealers in Bandung West Java. The method used in this research is empirical research through a mail survey. Data collection was conducted by using questionnaires in which Likert scale is used as the basis. The questionnaires were spread to 179 Dealer managers. The data which were collected, later on, were managed and were analyzed by using dual regression analysis (Multiple regression analysis) through the SPSS program. The result of this research shows that the participative budget, organization commitment, and work motivation give a positive influence on managerial performance. The significant influence of Participative Budget and Organization Commitment partially are about 0,044 and 0,000. The significant influence of Work Motivation on managerial performance partially is about 0,098. The significant influence of participative budget, organization commitment, and work motivation on managerial performance simultaneously are 0,000. It means that partially participative budget and organization commitment give significant positive influence on managerial performance, while work motivation gives insignificant positive influence on managerial performance.Â  Simultaneously, participative budget, organization commitment, and work motivation give significant positive influence on managerial performance.Â Â